Male and Female C57BL/6 Mice Respond Differently to Awake Magnetic Resonance Imaging Habituation - Lindhardt, Thomas Beck; Gutiérrez-Jiménez, Eugenio; Liang, Zhifeng; Hansen, Brian (Frontiers in Neuroscience, 2022)
Traditionally, preclinical magnetic resonance imaging (MRI) has been performed in anesthetized animals. However, anesthesia has been shown to perturb normal brain function and physiology. Such effects limit our ability to detect subtle physiological alterations in disease models and treatment studies, thus hampering discovery and compromising generality of findings. Therefore, methods for awake animal MRI are needed to study the rodent brain in its natural physiological state, free of anaesthetics. Current setups for awake animal MRI rely on restraining systems to avoid animal movement during scanning. To reduce restraint stress, animals are habituated to the scanner environment prior to MRI data collection. To date, however, most awake MRI studies employ male rodents only. This is a fundamental limitation as results obtained may be pertinent only to half of the population. We characterized training and habituation responses of male and female mice to provide improved, sex-dependent training procedures for awake mouse MRI. We recorded heart rate, monitored behavioral responses (body weight and fecal boli weight) and fecal corticosterone levels (FCM) as indicators of well-being and stress during a fourteen-day progressive habituation protocol. In addition, we also assessed discomfort levels and anxiety using the mouse grimace scale (MGS) and light/dark test (LDT), respectively. All scores were compared between both groups. We found that heart rate was significantly decreased after ten and eleven days of training for both males and females, respectively. However, the specific time course for this decrease was significantly different between males and females, and females exhibited higher anxiety levels during habituation and 14 days after habituation than to males. Lastly, we also found that mean FCM levels for both groups were decreased after eleven days of MRI habituation. The present work shows that mice can be successfully trained for extended MRI sessions which is necessary for many (particularly non-fMRI) studies. Importantly, we find that males and females differ in their response to awake MRI habituation, which should be considered in future awake MRI studies that aim to include male and female mice.